2018
DOI: 10.1371/journal.pgen.1007221
|View full text |Cite
|
Sign up to set email alerts
|

Conditional genetic screen in Physcomitrella patens reveals a novel microtubule depolymerizing-end-tracking protein

Abstract: Our ability to identify genes that participate in cell growth and division is limited because their loss often leads to lethality. A solution to this is to isolate conditional mutants where the phenotype is visible under restrictive conditions. Here, we capitalize on the haploid growth-phase of the moss Physcomitrella patens to identify conditional loss-of-growth (CLoG) mutants with impaired growth at high temperature. We used whole-genome sequencing of pooled segregants to pinpoint the lesion of one of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(90 reference statements)
1
10
0
Order By: Relevance
“…Results from Lang et al (2018) , where variance at genomic level was detected using the accessions Re, Vx and Ka, showed a SNP rate of one SNP per 1,783 bp for Re, per 644 bp for Ka and 188 bp for Vx while another study found a SNP rate of one SNP per 207 bp for Vx ( Ding et al, 2018 ). Similar results for the number of base pairs per SNP can be found for the RNA-seq analysis in this study (Re 1 SNP each 1,912 bp, Ka 630 bp and Vx 143 bp) ( Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results from Lang et al (2018) , where variance at genomic level was detected using the accessions Re, Vx and Ka, showed a SNP rate of one SNP per 1,783 bp for Re, per 644 bp for Ka and 188 bp for Vx while another study found a SNP rate of one SNP per 207 bp for Vx ( Ding et al, 2018 ). Similar results for the number of base pairs per SNP can be found for the RNA-seq analysis in this study (Re 1 SNP each 1,912 bp, Ka 630 bp and Vx 143 bp) ( Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of SNP segregation is a powerful tool that can be employed to analyze intra and inter accession fertility ( Perroud et al, 2011 , 2019 ; Meyberg et al, 2020 ), gene specific segregation patterns, and loci affected in segregants with specific traits. For example, the analysis of Gd and Vx segregants has been used to identify the ANR locus affected in mutants impaired in ABA hormone signaling ( Stevenson et al, 2016 ), as well as loci involved in three-dimensional morphogenesis [ nog 1, ( Moody et al, 2018 )] and a novel microtubule depolymerizing-end-tracking protein [ CLoG 1, ( Ding et al, 2018 )]. Most recently, SNPs between Gd and Re were associated with the loss of fertility in the Gd background ( Meyberg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, many studies have revealed that the development of tip growing cells in P. patens , and those of flowering plants, are regulated by common genetic mechanisms. P. patens is highly genetically tractable, largely due to the recent development of innovative techniques designed to identify mutations in sterile mutants generated by forward mutagenesis (X. Ding et al, 2018; Moody et al, 2018). Thus, future studies of the chloronema to caulonema transition will enable fundamental questions to be answered about the processes of stem cell formation, cell expansion, and differentiation across diverse taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The other study ( Fig 1 ), undertaken by Ding and colleagues [ 18 ] and reported in the May 2018 issue of PLOS Genetics , used temperature-sensitive (TS) growth mutants, which were blocked at an early stage of gametophytic development and were sterile at the restrictive temperature (32°C) but grew normally and were fertile at the permissive temperature (25°C). Although a few TS mutants of P .…”
mentioning
confidence: 99%